(untitled) (Research, Society and Development, 2021)
Food waste is understood as the intentional disposal of items for human consumption that occurs mainly in the last stages of the food production chain. Food waste can occur at all stages of the production process and, in the distribution stage, it involves prepared foods that are not consumed and the rest left by diners. Its volume reflects the quality of the service provided, therefore, it is important to monitor these values. Thus, we aim to identify the quantity of food waste in a University Restaurant. This is a temporal analysis carried out with data collected in three periods (2014, 2015 and 2016) in a restaurant of a Federal Institution of Higher Education. To assess waste, the Kruskal-Wallis test (Dunns post-hoc) was performed, adopting a significance level of 5%. It was observed that food waste did not meet the proposed recommendation of up to 15%, obtaining a value of 19.29%. The analysis showed significance for production values, per capita meals, leftovers and leftovers. Therefore, the high volume of food waste is possibly due to errors in planning, portion sizes, not using clean leftovers and lack of routine educational campaigns. The observed temporal variation may be a consequence of behavioral changes and the profile of students and employees of the company each year.